MANAJEMEN KEANDALAN DAN KETERSEDIAAN SISTEM DENGAN METODE GSLB (Global Server Load Balancing) - Atik Budi Paryanti; Ricco Aditya Marzuki (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2019)
Recently, The Directorate General of Customs and Excise provides public services 24 x 7 in customs and excise process, regarding of this, an information technology system which has a high level of availability and reliability is needed. To meet these needs, it is necessary to have GSLB technology (Global Server Load Balancing) which can be used to utilize resources in both data centers where the current system uses only one data center to provide website application services. By implementing GSLB technology (Global Server Load Balancing), traffic sharing can be done to both data centers and can reduce any risks if there is disruption in one of data center.